1972
DOI: 10.1063/1.1660922
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diluent mobility on the plasticization of polymers

Abstract: In an attempt to formulate a general picture of the influence of diluents on the physical properties of polymers without invoking specific molecular characteristics of the diluents, a systematic study has been undertaken of the mobility of both the polymer and the diluent in polymer-diluent systems, and of the resulting effects on the physical properties of these systems. In dynamic mechanical and dielectric loss studies of polymer-diluent systems, the influence of the mobility of the diluent on the background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The shear G and bulk K moduli are larger at temperatures well below the glass transition temperature, as one would generally expect from an enhancement of molecular packing by an additive; this trend inverts upon heating and the antiplasticized system actually becomes softer at elevated temperatures, as observed experimentally. 6,7,77,78 The crossing temperature for G was found to occur near the glass transition temperature of the pure polymer melt, while this temperature occurs at a higher temperature for K. The Poisson ratio n of the antiplasticized material becomes smaller in the glass state relative to the pure polymer melt and also exhibits a crossing temperature, a fact of relevance to recent attempts to correlate to the fragility of glass formation. 24,25,31,36 The crossing phenomenon means that the characteristic stiffening associated with antiplasticization has a limited temperature range in which it is observed, implying that such additives could readily be confused with plasticizer additives if measurements are only performed in the high temperature polymer melt state where the additive softens the material.…”
Section: Discussionmentioning
confidence: 86%
“…The shear G and bulk K moduli are larger at temperatures well below the glass transition temperature, as one would generally expect from an enhancement of molecular packing by an additive; this trend inverts upon heating and the antiplasticized system actually becomes softer at elevated temperatures, as observed experimentally. 6,7,77,78 The crossing temperature for G was found to occur near the glass transition temperature of the pure polymer melt, while this temperature occurs at a higher temperature for K. The Poisson ratio n of the antiplasticized material becomes smaller in the glass state relative to the pure polymer melt and also exhibits a crossing temperature, a fact of relevance to recent attempts to correlate to the fragility of glass formation. 24,25,31,36 The crossing phenomenon means that the characteristic stiffening associated with antiplasticization has a limited temperature range in which it is observed, implying that such additives could readily be confused with plasticizer additives if measurements are only performed in the high temperature polymer melt state where the additive softens the material.…”
Section: Discussionmentioning
confidence: 86%
“…This results in a decrease in free volume and a suppression of motion, particularly at the polymer chain ends. Other researchers have suggested that the key property of an antiplasticizer is its ability to specifically interact with the polymer (Petrie et al, 1972;Roy et al, 1987). In the more specific case of polymer-water interactions, a reduction in free volume has also been proposed as the reason for the observed increase in dynamic tensile modulus (E') on humidification of nylon films, while the systems were still in the glassy state (Prevorsek et al, 1971).…”
Section: Plasticization-antiplasticization In Synthetic Polymersmentioning
confidence: 99%
“…From dielectric investigations Ishida [33] has calculated an activation energy of 63 kJ/mol. The fl relaxation is attributed to a partial motion in the main chain of the polymer [34] and is particularly depressed if antiplasticizers are added [35] (Antiplasticizers are additives which increase the modulus and decrease the damping). The fl transition is seen as a marked step in the course of c~ in figure 10.…”
Section: Specific Volume Versus Temperature Curves At Constant Rate Omentioning
confidence: 99%